Design and Development of Ginna Digital Storytelling Media for Descriptive Text Instruction - Nurfajrin Ningsih, Dinni; Marinda Cysbya Erdlanda, Febry; Mulyanti, Sri; Sophia Salwa, Ginna (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study aims to design and develop digital storytelling media using Ginna for teaching descriptive texts. While digital storytelling has demonstrated effectiveness in various language learning contexts, there exists a significant research gap specifically in its application to descriptive text instruction, with no existing studies combining Ginna technology with digital storytelling for this pedagogical purpose. This research addresses critical educational challenges including limited digital-based learning tools in schools, restricted access to learning materials outside classroom hours, and low student participation rates. Method: The research employed a Research and Development (R&D) approach utilizing the ADDIE model (Analyze, Design, Development, Implementation, Evaluation) to systematically create and validate the digital storytelling media. Results: The developed media demonstrated exceptional feasibility across multiple validation measures. Material expert validation yielded an average score of 97.49%, while media expert validation achieved 92.49%, both categorized as "very feasible." Student response evaluation further confirmed the media’s effectiveness with an outstanding average score of 97.79%. Novelty: This study contributes a novel integration of Ginna technology into digital storytelling for descriptive text instruction, creating an innovative educational medium that significantly enhances student engagement while providing unprecedented accessibility to learning resources beyond traditional classroom constraints.